Toward a framework for understanding Black male athlete social responsibility (BMASR) in big-time American sports. (1st January 2011) - Agyemang, Kwame J.A.; Singer, John N.
Stemming from their commodification as a means for growing sport into a commercial entity, multi-million dollar professional contracts with teams and sponsors, and sometimes, socially (un)acceptable acts, current Black male professional athletes in big-time American sports face not only the pressure to perform athletically, but also to conduct themselves in a socially responsible manner. Given the above mentioned factors, this paper sees today's Black male athlete as a business, therefore necessitating them to engage in socially responsible acts as a means of management, just as scholars have encouraged CSR initiatives, among many strategies, to manage a corporation. Answering the call of sport management scholars to further analyse and expand CSR principles in sport, the purpose of this paper is to illuminate on Black male athlete social responsibility (BMASR) as a management strategy with the intention of moving toward a framework for understanding this concept.